2021
DOI: 10.3390/su13074066
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of External and Internal Factors on Competitive Advantage—Moderation of Market Dynamism and Mediation of Customer Relationship Building

Abstract: Using a resource-based view and dynamic capabilities approach, this study investigates both the internal and external factors influencing competitive advantage in the hotel industry. For this purpose, we examine how organizational capabilities may lead to customer relationship building and in turn to competitive advantage. We further test the moderation role of market dynamism on the relationship between organizational capabilities and customer relationship building, and also investigate the mediation effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The results indicate that idea generation (indirect effect = 0.311, lower level confidence interval (LLCI) = 0.219, and upper‐level confidence interval (ULCI) = 0.400, P < 0.001), concept definition (indirect effect = 0.467, LLCI = 0.359, and ULCI = 0.582, P < 0.001), and initial planning (indirect effect = 0.364, LLCI = 0.262, and ULCI = 0.475, P < 0.001) mediate the effect of innovation orientation on competitive advantage. The values of LLCI and ULCI are both positive and the bootstrapped confidence interval does not include zero (Cheraghalizadeh et al, 2021). Thus, H3a, H3b, and H3c are supported.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that idea generation (indirect effect = 0.311, lower level confidence interval (LLCI) = 0.219, and upper‐level confidence interval (ULCI) = 0.400, P < 0.001), concept definition (indirect effect = 0.467, LLCI = 0.359, and ULCI = 0.582, P < 0.001), and initial planning (indirect effect = 0.364, LLCI = 0.262, and ULCI = 0.475, P < 0.001) mediate the effect of innovation orientation on competitive advantage. The values of LLCI and ULCI are both positive and the bootstrapped confidence interval does not include zero (Cheraghalizadeh et al, 2021). Thus, H3a, H3b, and H3c are supported.…”
Section: Resultsmentioning
confidence: 99%
“…The new business environment demands greater attention be paid to internal and external factors, especially those that impact firms’ sustainability and competitiveness (Cheraghalizadeh, Olya, & Tumer, 2021). García-Villaverde et al (2020) hold that market dynamism is characterized by rapid changes in consumers’ tastes and needs, while also having a significant effect on corporate practice, and hence, it is recommended that greater attention be focused on market variations.…”
Section: Review Of the Literature And Hypotheses Developmentmentioning
confidence: 99%
“…Our review of the literature identified several works on the direct and indirect effects of market dynamism (García-Villaverde et al , 2020; Cheraghalizadeh et al , 2021), yet studies linking it to structural adaptation and pioneering behavior are scarce. Furthermore, it has been the subject of limited analysis in the field of tourism firms in developing economies (Zhang & Zhang, 2018).…”
Section: Review Of the Literature And Hypotheses Developmentmentioning
confidence: 99%
“…Lastly, a mutually advantageous exchange is a crucial prerequisite for a successful relationship (Alshurideh et al, 2022;Kozak & Buhalis, 2019). If there are no shared benefits, the association is more manipulative; an example is database marketing's unilateral relationship-building tactics, which do not require client approval (Cheraghalizadeh et al, 2021;Crittenden et al, 2014). Relationships are built on trust and satisfaction, and if one person is not happy with the other's manipulative behaviour, then there will be no trust, and there will not be any interdependence between the two parties.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%